VERIFICATION OF THE PIPELINE DEFORMATIONAL MODEL IN NON-STANDARD SOIL CONDITIONS (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
This paper discusses existing methods for evaluating longitudinal stresses in the pipeline caused by uneven deformations of soil base; which is composed by soils with special properties. Verification of the pipeline design scheme have been performed. In research we based on the results of the previous experimental and theoretical investigations, data of the engineering inspections of the existing main pipeline above ground crossing. Comparison of the longitudinal stresses calculated by different methods have been done. Hypothesis that pipeline deformations are equal to the deformations of the soil base is confirmed. With help of numerical modeling by finite element method we obtained differential settlements of the loessial collapsible strata; which occur during the soaking of the soil local area. Respective longitudinal stresses have been calculated.
Keywords: model verification; pipeline above ground crossing; karst cavities; loessial collapsible soil basis; pipeline stiffness; external loads and influences; longitudinal stresses